2023
DOI: 10.3390/vetsci10030228
|View full text |Cite
|
Sign up to set email alerts
|

Determining Frequency of Common Pulmonary Gross and Histopathological Findings in Feedyard Fatalities

Abstract: Pulmonary disease is often associated with feedlot cattle mortality, and the most common syndromes include bronchopneumonia, acute interstitial pneumonia, and bronchopneumonia with an interstitial pneumonia. The study objective was to utilize gross necropsy and histopathology to determine the frequency of pulmonary lesions from three major syndromes and agreement between gross and histopathological diagnosis. A cross sectional, observational study was performed at six U.S. feedyards using a full systematic nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One relatively novel area for this study was the classification of BIP as the combination of gross pulmonary pathologies of BP and AIP. Previous research in the U.S. and Canada showed that BIP was present in about two-thirds of feedyard cattle presenting pulmonary lesions at necropsy [ 16 , 17 ]. Nevertheless, investigations of the epidemiological characteristics associated with BIP are scarce for U.S. feedyard cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One relatively novel area for this study was the classification of BIP as the combination of gross pulmonary pathologies of BP and AIP. Previous research in the U.S. and Canada showed that BIP was present in about two-thirds of feedyard cattle presenting pulmonary lesions at necropsy [ 16 , 17 ]. Nevertheless, investigations of the epidemiological characteristics associated with BIP are scarce for U.S. feedyard cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers reported the simultaneous presence of AIP and BP in deceased feedyard cattle. A new classification has been suggested as bronchopneumonia with an interstitial pneumonia (BIP) due to the presence of lesions compatible with AIP in caudodorsal lobes and BP on cranioventral lobes [ 16 , 17 , 18 , 19 ]. In previous studies when lesions consistent with BIP were found during necropsy, the final diagnosis or cause of death was limited to AIP or BP only, and it was dependent on the pathology that affected the majority of the lung [ 14 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation